Anti-tumor activity of a B-cell receptor-targeted peptide in a novel disseminated lymphoma xenograft model - Wehr, Claudia; Müller, Fabian; Schüler, Julia; Tomann, Tina; Nitschke, Claudia; Seismann, Henning; Spillner, Edzard; Klingner, Kerstin; Schneider-Merck, Tanja; Binder, Mascha; Fiebig, Heinz Herbert; Mertelsmann, Roland; et al. (International Journal of Cancer, 2012)
Receptor-targeted therapies have become standard in the treatment of various lymphomas. In view of its unparalleled specificity for the malignant B-cell clone, the B-cell receptor (BCR) on B cell lymphoma cells is a potential therapeutic target. We have used two BCR epitope mimicking peptides binding to the Burkitt's lymphoma cell lines CA46 and SUP-B8. We proved their functionality by demonstrating calcium flux and BCR-mediated endocytosis upon peptide receptor binding. Toxicity experiments in vitro via cross-linking of the BCR with tetramerized epitope mimics lead to apoptosis in both cell lines but was far more effective in SUP-B8 cells. We established a SUP-B8-based disseminated Burkitt's lymphoma model in NOD/SCID mice. Treatment of tumor-bearing mice with tetramerized epitope mimics had significant anti-tumor effects in vivo. We conclude that peptide-mediated, BCR-targeted therapy is a promising approach which may be explored and further developed for application in highly aggressive lymphoma. Copyright © 2011 UICC.
CRIS-Team Scopus Importer:2024-12-02
Keywords: B-cell receptor; Burkitt's lymphoma; epitope mimic; phage display; xenograft model